Developing Leadership Culture in the Context of the Fourth Industrial Revolution: Theory and Practice - Thanh, Pham Ngoc (VNU Journal of Science: Policy and Management Studies; Vol 34 No 1DO - 10.25073/2588-1116/vnupam.4136, 2018)
Abstract: This paper focuses on the impact of the Fourth Industrial Revolution on the development of leadership culture through the analysis of the relationship between leadership culture and industrial revolutions. Furthermore, the article addresses the methodological issues of developing leadership culture under the impact of the Fourth Industrial Revolution. Keywords: Leadership culture, cultural leadership, the Fourth Industrial Revolution